Pengaruh Kegiatan Ekstrakurikuler Baca Tulis Alquran (BTQ) Terhadap Afektif Siswa Sekolah Dasar - Ramdan Samadi, Mochammad; Yudiyanto, Mohamad; Jonaidi (Prodi PGMI STAI Sabili Bandung, 2023)
Extracurricular Alquran Reading and Writing activities are crucial as they help elementary school students understand moral and spiritual values. These activities contribute to the affective development of students by enhancing their motivation, discipline, and sense of responsibility through structured and meaningful learning. This study aims to analyze the impact of extracurricular Alquran Reading and Writing activities on the affective development of elementary school students. Using a qualitative approach with a literature review method, the study explores various relevant sources. The findings indicate that Alquran Reading and Writing activities have a significantly positive impact on students' affective aspects, including increased motivation, discipline, and spiritual attitudes. Support from teachers and family environments plays a vital role in the effectiveness of these activities. These findings highlight the importance of integrating religion-based extracurricular activities into the elementary school curriculum to support students' holistic affective development.